The Development of the "Two Trolley Technique" for Supine Positioning in a Patient with a Penetrating Spinal Trauma - Asish Karthik; P. S. Shijin; Prabhleen Kaur; Rini Sara Varghese; C. H. Aiswarya (Research Developments in Medicine and Medical Science Vol. 2, 2023)
The present study discusses the anaesthetic management of this unusual case and the development of the "Two Trolley Technique" for supine positioning, a deviance from recommended intubation techniques for penetrating back trauma. Due to the inability to position supinely, penetrating trauma to the back presents the anaesthesiologist with numerous challenges in managing the airway and obtaining central lines. Although earlier descriptions of lateral position intubation for the same purpose exist, it is still unfamiliar. We can restrict the mobility of the penetrating object and, at the same time, not deviate to the uncommon domain of lateral position intubation.